Solving late for relief event in bus crew rescheduling using multi agent system - Abdul Rahman, Ahmad Fadzli Nizam; Shibghatullah, Abdul Samad; Abal Abas, Zuraida; Eldabi, Tillai; Chit, Su Mon; Amir Hussin, Amir Aatieff (School of Engineering, Taylor's University, 2020)
Unpredictable event is an event which happens anytime without notice that will disrupt bus services. Bus crew is one of the causes of the unpredictable event. For example, if a bus crew comes late – s/he will cause certain bus to depart late. In this paper, three types of lateness are defined: Late For Sign-On, Late For Relief , and Late For Second Work. However this paper will only discuss the solution for LFR type. When LFR happens, the schedule needs to be rescheduled. Currently, there is no automated mechanism to handle LFR issue especially in Internet of Thing (IoT) environment. Most real time rescheduling approaches are not supported due to static schedules constraint. Mathematical approaches require extensive computational power, therefore delaying real-time results. Meanwhile, manual rescheduling is prone to error and not optimum. The objective of this paper is to implement a new approach in automating the bus crew rescheduling process in IoT environment by using a Multi-Agent System for LFR event. The agents dynamically adapt their behaviour to changing environments quickly and find solutions via negotiations and cooperation between them in IoT. Experiment is conducted using the AgentPower simulation tool. The result concluded that the proposed technique is capable of quick rescheduling in bus crew rescheduling in the LFR event.